2020
DOI: 10.1021/acs.biochem.9b01037
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Selective Cytotoxicity of a Fluorescent Rhodium Metalloinsertor Conjugate Results from Irreversible DNA Damage at Base Pair Mismatches

Abstract: Up to twenty percent of solid tumors are characterized by DNA mismatch repair (MMR) deficiency and microsatellite instability (MSI) that confer resistance to standard of care chemotherapy. MMR-deficient cancers have an increased mutation rate and accumulate DNA mismatches. We previously described a class of compounds, rhodium metalloinsertors, that bind DNA mismatches with high specificity and selectivity and have potential as targeted therapy. [Rh(chrysi)(phen)(PPO)] 2+ (RhPPO) is the most potent, selective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…We have designed and characterized rhodium metalloinsertors which bind specifically to DNA mismatches and as a result induce selective toxicity within MMR-deficient cancer cell lines ( 16 , 22 , 23 , 31 33 ). In addition, various ruthenium complexes have been designed and synthesized as chemotherapeutics, although with different biological targets ( 21 , 34 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have designed and characterized rhodium metalloinsertors which bind specifically to DNA mismatches and as a result induce selective toxicity within MMR-deficient cancer cell lines ( 16 , 22 , 23 , 31 33 ). In addition, various ruthenium complexes have been designed and synthesized as chemotherapeutics, although with different biological targets ( 21 , 34 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that RhPPO-Cy3 displayed selective luminescence upon binding to mismatched DNA in vitro , with a binding affinity, K B (CC), of 1.8 × 10 6 M –1 , comparable to that of unconjugated RhPPO (5.4 × 10 6 M –1 ) . RhPPO-Cy3 also maintained high potency and selectivity for MMR-deficient cells . Thus, the properties of RhPPO-Cy3 enabled further study of rhodium metalloinsertor activity at DNA mismatches in cells.…”
Section: Rhodium Metalloinsertors: Cellular Mechanism Of Actionmentioning
confidence: 80%
“…RhPPO-Cy3 formed nuclear foci in MMR-deficient cells, demonstrating for the first time that a rhodium complex localizes to genomic DNA (Figure ). Furthermore, the RhPPO-Cy3 foci showed partial overlap with DNA damage-induced foci containing pH2AX and Rad51 . In addition to H2AX phosphorylation, RhPPO-Cy3 binding also induced phosphorylation of the checkpoint protein kinase Chk1.…”
Section: Rhodium Metalloinsertors: Cellular Mechanism Of Actionmentioning
confidence: 96%
See 1 more Smart Citation
“…For selectively detection of DNA mismatches, Barton and colleagues conjugated Cy3 to two slightly different rhodium metalloinsertors, i.e., [Rh(phen)(chrysi)(HDPA)] 3+ ( 58 ) and [Rh(PPO)(chrysi)(HDPA)] 2+ ( 59 ) (Figure 10h). [ 87 ] Both probes displayed an enhanced fluorescence emission toward single‐mismatched DNA and were able to differentiate the MMR‐deficient versus MMR‐proficient phenotype in genomic DNA extraction and living cells, respectively. Additionally, 59 could induce irreversible DNA damage at or near mismatched site (Figure 10h) and possessed limited cytotoxicity for MMR‐deficient HCT‐116 O cells (EC 50 = 1.0 × 10 −6 ± 0.1 × 10 −6 m ).…”
Section: Probes For Targeted Fluorescence Imagingmentioning
confidence: 99%